Nuclear dimension of simple C*-algebras - Castillejos, J; Evington, S; Tikuisis, A; White, S; Winter, W (Springer, 2020)
We compute the nuclear dimension of separable, simple, unital, nuclear, Z-stable C*-algebras. This makes classification accessible from Z-stability and in particular brings large classes of C*-algebras associated to free and minimal actions of amenable groups on finite dimensional spaces within the scope of the Elliott classification programme.